A stay of execution: ATF4 regulation and potential outcomes for the integrated stress response - Neill, Graham; Masson, Glenn R. (Frontiers in Molecular Neuroscience, 2023)
ATF4 is a cellular stress induced bZIP transcription factor that is a hallmark effector of the integrated stress response. The integrated stress response is triggered by phosphorylation of the alpha subunit of the eukaryotic initiation factor 2 complex that can be carried out by the cellular stress responsive kinases; GCN2, PERK, PKR, and HRI. eIF2α phosphorylation downregulates mRNA translation initiation en masse, however ATF4 translation is upregulated. The integrated stress response can output two contradicting outcomes in cells; pro-survival or apoptosis. The mechanism for choice between these outcomes is unknown, however combinations of ATF4 heterodimerisation partners and post-translational modifications have been linked to this regulation. This semi-systematic review article covers ATF4 target genes, heterodimerisation partners and post-translational modifications. Together, this review aims to be a useful resource to elucidate the mechanisms controlling the effects of the integrated stress response. Additional putative roles of the ATF4 protein in cell division and synaptic plasticity are outlined.